An assessment of mode-coupling and falling-friction mechanisms in railway curve squeal through a simplified approach. (9th June 2018) - Ding, Bo; Squicciarini, Giacomo; Thompson, David; Corradi, Roberto
Abstract: Curve squeal is one of the most annoying types of noise caused by the railway system. It usually occurs when a train or tram is running around tight curves. Although this phenomenon has been studied for many years, the generation mechanism is still the subject of controversy and not fully understood. A negative slope in the friction curve under full sliding has been considered to be the main cause of curve squeal for a long time but more recently mode coupling has been demonstrated to be another possible explanation. Mode coupling relies on the inclusion of both the lateral and vertical dynamics at the contact and an exchange of energy occurs between the normal and the axial directions. The purpose of this paper is to assess the role of the mode-coupling and falling-friction mechanisms in curve squeal through the use of a simple approach based on practical parameter values representative of an actual situation. A tramway wheel is adopted to study the effect of the adhesion coefficient, the lateral contact position, the contact angle and the damping ratio. Cases corresponding to both inner and outer wheels in the curve are considered and it is shown that there are situations in which both wheels can squeal due to mode coupling. Additionally, a negative slope is introduced in the friction curve while keeping active the vertical dynamics in order to analyse both mechanisms together. It is shown that, in the presence of mode coupling, the squealing frequency can differ from the natural frequency of either of the coupled wheel modes. Moreover, a phase difference between wheel vibration in the vertical and lateral directions is observed as a characteristic of mode coupling. For both these features a qualitative comparison is shown with field measurements which show the same behaviour.